Study on maintenance of Federal Road / Nur Muhammad Hatta Suleiman - Suleiman, Nur Muhammad Hatta (2007)
The poor condition at Malaysia's road is an old issue. It always issued but it still in same condition. This problem occurs due to the increasing numbers of vehicles recently, lack of provision and poor maintenance work. The command problems is damage to the road, such as hole, billowy surface, underground pipe leaking which is can cause holes at pavement, out of condition of road's furniture, unleveled road's shoulders and blockage drainage. These command problems will causes the road become dirtier and bring problems to the users. Among other new issues are, metal scrap from lorry, scatted on the road surface. It's becoming problem to other user such as puncture and may cause an accident. This dissertation almost focusing to find parties who were responsible to carry out the maintenance works to the Federal Road especially at the Central and East Zone, which can be looking through theirs scope of maintenance works and how they implement the maintenance. This dissertation is also found the command road's problem, the maintenance schedule and budget. To clearly this topic, this dissertation was enclosed with three (3) case studies; 1. Route 5 (Banting - Klang), 2. Route 5 (Klang - Kuala Selangor), 3. Route 3214 (Sg. Buloh - Batu3, Shah Alam.